Three patients with DeSanto‐Shinawi syndrome: Further phenotypic delineation. Issue 6 (16th April 2018) - Uehara, Tomoko; Ishige, Takashi; Hattori, Shigeto; Yoshihashi, Hiroshi; Funato, Michinori; Yamaguchi, Yu; Takenouchi, Toshiki; Kosaki, Kenjiro
Abstract : Somatic truncating variants of the WAC gene have been observed in patients with hematologic malignancies. Furthermore, de novo heterozygous constitutional pathogenic variants of WAC have recently been shown to cause a syndromic form of intellectual disability, DeSanto‐Shinawi syndrome. It is unknown whether the constitutional pathogenic variants observed in the intellectual disability syndrome overlap with the somatic pathogenic variants observed in hematologic abnormalities. Herein, we report three patients with constitutional truncating variants of WAC in an attempt to address the above questions. All three of the patients had mild to moderate intellectual disability and dysmorphic features. We then reviewed the phenotypic features of 19 patients with DeSanto‐Shinawi syndrome, including the three currently reported ones: eight and seven patients showed a bulbous nasal tip and short fingers, respectively. As for the pathogenetic mechanism, we demonstrated that the expression level of the mRNA derived from the wildtype allele was higher than that derived from the mutated allele, demonstrating nonsense‐mediated mRNA decay. This observation makes a haploinsufficiency mechanism likely. Reviews of the constitutional and somatic pathogenic variants observed in patients with hematologic malignancies showed a significant overlap of the two. To date, no patients with DeSanto‐Shinawi syndrome have been reported to have developed hematologic abnormalities, except for one of the three patients reported herein who developed leukopenia and thrombocytopenia at the age of 19 years. Larger data sets are required to determine hematologic prognosis of patients with constitutional WAC variants.